The roles of attitude, subjective norms and perceived behavioural control towards family takaful insurance purchase intention: a case study at Jalan Tuanku Abdul Rahman, Kuala Lumpur/ Puteri Aliah Farhana Anuar and Juliana Jamal - Anuar, Puteri Aliah Farhana; Jamal, Juliana (Faculty of Business and Management, 2016)
The aim of this research was to analyze which factors that affect purchase intention of consumer toward Family Takaful insurance. In this study, it analyze which factors that can affect purchase intention of consumer toward Family Takaful insurance based on the roles of attitude, subjective norms and perceived behavioral control especially at Jalan Tuanku Abdul Rahman area. The insurance sector in Malaysia had shown rapid growth in recent years. However, the rapid growth in insurance sector can only been seen in conventional insurance rather than takaful insurance. So, it is crucial to know which factors that affect the consumer’s purchase intention towards Takaful insurance scheme. The data were gathered using 150 set of questionnaires as it were distributed at Jalan Tuanku Abdul Rahman, Kuala Lumpur, Malaysia. The data were interpreted using multiple regression analysis to explain the relationship between attitude, subjective norms and perceived behavioral control with consumer’s intention towards purchasing Family Takaful Insurance. The most factors that influence the consumer’s intention towards purchasing Family Takaful Insurance was subjective norms and followed by attitude and perceived behavioral control. As overall, there was significant relationship between dependent variable and independent variables. Based on this study, it was a good opportunity to understand the consumer’s purchasing intention towards Family Takaful Insurance in Malaysia. The marketers will be able to use this data as an indicator to make them have a clear idea about consumer’s preferences.